Awareness of Emotional Expressions in Cannabis Users: An Event-Related Potential Study - Torrence, Robert D.; Rojas, Donald C.; Troup, Lucy J. (Frontiers in Psychology, 2019)
Cannabis use has been associated with anxiogenic effects when used in low frequency for a short duration, but cannabis can also have anxiogenic effects when used heavily for a long duration. Animal studies have indicated the neurobiological mechanisms related to cannabis and anxiety; however, research has been limited on the related neurocognitive mechanisms. Previous research has indicated that cannabis use is associated with alterations in event-related potentials (ERPs). The purpose of the current study was to examine anxiety related attentional processing of emotional expressions using ERP methods. We used a backward masking paradigm to restrict awareness of facial expressions (i.e. fearful, happy, and neutral). The results indicated that cannabis use was associated with differences in emotional processing. Specifically, the results suggested cannabis users had increased P1 amplitudes towards happy facial expressions compared to fearful and neutral. Additionally, cannabis users seemed to have reduced N170 hemisphere lateralization. Key words: Cannabis, ERP, Emotion, Facial Expression, Awareness